Perbandingan Metode Quasi Monte Carlo Dengan Barisan Kuasi-Acak Halton Dan Barisan Kuasi-Acak Sobol Dalam Option Pricing - Stanislaus S Uyanto (Majalah Ilmiah Ekonomi Komputer, 2007)
The Monte Carlo method has proved to be a valuable tool for estimating security prices for which closed form solutions do not exist. This paper evaluate te Quasi-Monte Carlo method that has attractive properties for the numerical valuation of derivatives and examines the use of Monte Carlo simulation with low-discrepancy sequences for valuing derivatives versus the traditional Monte Carlo method using pesudo-random sequences. The relative performance of the methods is evaluated based on European options. Keywords : Monte Carlo, Quasi-Monte Carlo, European options